Additional Halogenated Secondary Metabolites from the Sea Hare Aplysia dactylomela - C.S, Vairappan; S.P, Anangdan; K.L, Tan (Malaysian Journal of Science, 2007)
As part of our continuous interest in the presence of secondary metabolites in marine flora and fauna of Borneo, we investigated the chemical composition of sea hare (Aplysia dactylomela) collected from Sepanggar Island, Kota Kinabalu. Five halogenated secondary metabolites were isolated and identified as; Palisadin A (1, 2%), Aplysistatin (2, 16%), 5-acetoxypalisadin B (3, 2%), Palisadin B (4, 4%) and 12-hydroxypalisadin B (5, 2%). Similar analysis of its diet, Laurencia snackeyi, indicated the presence of compounds 1, 2, 3 and 4 only. The presence of the additional compound, 12-hydroxypalisadin B (2) is suggested to be a derivative compound due to chemical modification of Palisadin B (4) in the gut of the sea hare and can be explained through biogenesis. Isolated compounds also showed various levels of antimicrobial activities against environmental and clinical microbes.